﻿Evaluation of the pharmacological activity of hybrid organotin compounds in a B16 melanoma model in the classical and metronomic administration modes - Margarita A. Dodokhova; Andrey V. Safronenko; Inga M. Kotieva; Margarita S. Alkhuseyn-Kulyaginova; Dmitry B. Shpakovsky; Elena R. Milaeva (Belgorod National Research University, 2022)
Introduction: In modern medical chemistry, much attention is paid to the search for new antimetastatic agents based on metal compounds. Organotin compounds promise to be good candidates as the treatment of malignant neoplasms. In order to reduce a possible nonspecific toxic effect of tin compounds and to expand the intended therapeutic use, the paper presents hybrid tin (IV) complexes with Sn-S bond containing a fragment of 2,6-di-tert-butylphenol. The aim of the study was to evaluate the antitumor and antimetastatic effects of bis (3,5-di-tert-butyl-4-hydroxyphenylthiolate) dimethylolol (Me3) and (3,5-di-tert-butyl-4-hydroxyphenylthiolate) triphenylolol (Me5) in a model of transplanted melanoma tumor in B16 mice in classical and metronomic administration mode. Materials and methods: The efficacy of organotin compounds was studied in a model of a transplanted tumor with spontaneous metastasis of C57Bl/6 (female) melanoma B16 mice using the following indicators: average life expectancy, inhibition of tumor growth by weight, tumor mass, and metastasis inhibition index. Results and discussion: The most pronounced antimetastatic effect (54% and 36%) is achieved with a five-fold intraperitoneal injection of Me3 and Me5 at the total doses of 375 mg/kg and 250 mg/kg. The comparable results of the efficacy were obtained in the classical and metronomic modes of the injection of hybrid organotin compounds. With an increase in the injected dose, there is an effect of activating the tumor process with the generalized metastasis. Conclusion: Bis dimethylolol (Me3) and triphenylolol (Me5) compounds demonstrate both a pronounced antimetastatic activity and a multidirectional effect on the growth of the primary focus and the metastasis in lungs, depending on an injected dose.